The Effect of Brand Image and Perceived Security on QRIS User Loyalty in the DANA E-Wallet through Perceived Risk as an Intervening Variable (Case Study of Students at Universitas Muhammadiyah Pontianak) - Daffa Avila Aprilian; Fenni Supriadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of Brand Image and Perceived Security on QRIS User Loyalty with Perceived Risk as an intervening variable among students of Universitas Muhammadiyah Pontianak. The study uses a quantitative approach with an associative design. The research population is students of Universitas Muhammadiyah Pontianak who use QRIS on the Dana e-wallet, with a sample of 100 respondents determined through purposive sampling according to the criteria of Dana usage and the intensity of QRIS transactions. Primary data were collected through questionnaires, while secondary data were sourced from official publications related to QRIS development. Data analysis used PLS-SEM with SmartPLS through evaluation of the outer model (convergent validity, discriminant validity, AVE, and reliability) and the inner model (R-square, F-square, and SRMR), accompanied by hypothesis testing through direct effect and indirect effect (bootstrapping). The results show that all constructs meet the validity and reliability criteria. The model has a good fit with SRMR = 0.064 and the model’s explanatory ability is in the moderate category (R² loyalty = 0.639; R² perceived risk = 0.564). Structurally, Brand Image has a significant positive effect on Loyalty (t = 4.280; p = 0.000), while Perceived Security is not significant on Loyalty (p = 0.183). Perceived Risk has a significant negative effect on Loyalty (t = 2.246; p = 0.025), but Brand Image and Perceived Security are not significant on Perceived Risk. In addition, Perceived Risk does not mediate the effect of Brand Image or Perceived Security on QRIS user loyalty.